«Перший крупний жіночий внесок в етнографію»: Софія Чернявська - Іваннікова, Л. (Народна творчість та етнологія, 2018)
У статті вперше в історії української фольклористики розглянуто науковий доробок маловідомої збирачки фольклору Херсонщини. Автор дав оцінку її праці з погляду сучасної науки, зосередив увагу на малодосліджених явищах традиційної культури, які зафіксувала С. Чернявська, зокрема, проводи до війська, вірування про перетворення води на вино тощо; ввів у науковий обіг фольклористики записи легенд, зроблені в XVII ст. For the first time in the history of Ukrainian folklore studies, the article considers the scientific contribution of a little-known collector of the Khersonshchyna folklore, Sofiya Cherniavska. The authoress gives an evaluation of her work from a modern science point of view. She focuses on scantily explored phenomena of traditional culture recorded by the collector, in particular, the send-off to the army, beliefs on the transformation of water into wine, etc. She also introduces records of legends made in the XVIIth century into the scientific circulation of folklore studies.